2020
DOI: 10.17511/jopm.2020.i01.03
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and trends in transfusion transmitted infections in blood donors: a 6-year experience in a tertiary care hospital

Abstract: Introduction: Blood transfusion continues to be a possible source of pathogens in transfused patients. The pattern of transfusiontransmitted infections (TTI) varies between regions. Knowledge of prevalence of TTIs is essential to monitor safety of blood transfusion by ensuring better practices of collection and processing of blood components. The aim of the study was to determine the prevalence of TTI in blood donors in a tertiary care hospital in central India. Materials and Methods: A retrospective cross sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…In the present study, the seroprevalence of HCV was found to be 0.63% (Table 2 ). As compared to our study, the seroprevalence of HCV was reported in blood donors in other parts of India by Garg et al (0.28%) from western India [ 26 ], Mandal et al (0.62%) from Darjeeling [ 35 ], Jindal et al (1.76%) from north India [ 36 ], Saini et al (0.07%) from Indore [ 33 ], Mukherjee et al (0.044%) from western Odisha [ 37 ], Shaiji et al (0.72%) from Trivandarum [ 38 ], Meena et al (0.57%) from Delhi [ 39 ], Pahuja et al (0.66%) from Delhi [ 22 ], Kaur et al (2.44%) from North India [ 29 ], Afrose et al (0.22%) from Aligarh [ 40 ], Ryhan et al (0.22%) from Srinagar [ 32 ], Shah et al (0.33%) from Ahmedabad [ 34 ], Gupta et al (1.45%) from Ludhiana [ 41 ], Bagde et al (0.065%) from Rajnandgaon, Chhattisgarh [ 42 ], Pawan et al (0.50%) from Delhi [ 25 ], Sawke et al (0.57%) from Bhopal [ 43 ], Patel et al (0.14%) from Gujarat India [ 44 ], and Dhariwal et al (0.71%) from Rajasthan [ 31 ]. However, reported seroprevalence of HCV in countries other than India was given by Abebe et al (0.64%) from Western Oromia, Ethiopia [ 45 ], Mobarki et al (1.09%) from Jazan region of Saudi Arabia [ 46 ], Ahmed et al (1.75%) from Karachi, Pakistan [ 47 ], and Alharazi et al (2.0%) from Sana’a, Yemen [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the seroprevalence of HCV was found to be 0.63% (Table 2 ). As compared to our study, the seroprevalence of HCV was reported in blood donors in other parts of India by Garg et al (0.28%) from western India [ 26 ], Mandal et al (0.62%) from Darjeeling [ 35 ], Jindal et al (1.76%) from north India [ 36 ], Saini et al (0.07%) from Indore [ 33 ], Mukherjee et al (0.044%) from western Odisha [ 37 ], Shaiji et al (0.72%) from Trivandarum [ 38 ], Meena et al (0.57%) from Delhi [ 39 ], Pahuja et al (0.66%) from Delhi [ 22 ], Kaur et al (2.44%) from North India [ 29 ], Afrose et al (0.22%) from Aligarh [ 40 ], Ryhan et al (0.22%) from Srinagar [ 32 ], Shah et al (0.33%) from Ahmedabad [ 34 ], Gupta et al (1.45%) from Ludhiana [ 41 ], Bagde et al (0.065%) from Rajnandgaon, Chhattisgarh [ 42 ], Pawan et al (0.50%) from Delhi [ 25 ], Sawke et al (0.57%) from Bhopal [ 43 ], Patel et al (0.14%) from Gujarat India [ 44 ], and Dhariwal et al (0.71%) from Rajasthan [ 31 ]. However, reported seroprevalence of HCV in countries other than India was given by Abebe et al (0.64%) from Western Oromia, Ethiopia [ 45 ], Mobarki et al (1.09%) from Jazan region of Saudi Arabia [ 46 ], Ahmed et al (1.75%) from Karachi, Pakistan [ 47 ], and Alharazi et al (2.0%) from Sana’a, Yemen [ 48 ].…”
Section: Discussionmentioning
confidence: 99%